Are fiscal rules helpful in mitigating the impact of oil market fluctuations? - Fuad Mammadov; Adigozalov Shaig (Graduate Institute of International and Development Studies, 2017)
In this paper we empirically examined the role of fiscal rules in mitigating the impact of oil market fluctuations in resource-rich economies using a structural panel VAR framework following P. Pedroni (2013) and incorporating identification scheme of Kilian (2009). Our key findings can be summarized as: l) oil exporting developing countries exhibit procyclical respond to positive oil market specific demand shock, 2) there are significant crosscountry differences in the way governments respond to the oil market shocks, 3) fiscal rules mitigate the shocks and generate fiscal discipline only if when all fiscal rules are imposed simultaneously, 4) we couldn't identify any significant role of wealth funds as a budget stabilization policy.
Keywords: C12; C22; C23; E62; 330; fiscal rule; structural panel VAR; oil shocks